The Analysis of Conversational Implicature in an Extensive Listening of BBC Learning English Podcast - Retno Dwiwulandari; Ratna Dewanti (Stairs, 2020)
Using qualitative content analysis, this study attempts to investigate the occurrence of conversational implicature in an extensive listening of BBC Learning English Podcast. This study was conducted to find out how conversational implicature is employed by the speakers, including the types and functions of the implicature. Following Grice’s theory of conversational implicature and cooperative principle, this study revealed that out of 200 samples taken, the implicature occurred in 104 utterances which were generated through flouting and violation with Particularized Conversational Implicature (PCI) dominating the exchange rather than Generalized Conversational Implicature (GCI). As for the function of implicature produced, the researcher utilized Searle’s theory of Speech Act which comprises Assertive, Commissive, Declarative, Directive, and Expressive. The result showed that Assertive function dominates the utterance produced, meanwhile Declarative function was absent. The findings and result of this study is expected to be able to give some instances to the learners of English to the theory of conversational implicature, so that they will learn to avoid misunderstanding during the conversation itself. It is also expected to give contribution to the field of pragmatics, since, to the researcher’s knowledge, the study of conversational implicature on the same media is still scarcely conducted.